Method for eliminating residual alkali of high-nickel ternary positive electrode material

By forming a coating layer of cobalt tetroxide on the surface of the high-nickel ternary cathode material, the problem of difficult elimination of residual lithium compounds is solved, the cycle stability and conductivity of the battery are improved, and the performance of the battery in fast charging and high power output scenarios is improved.

CN119330413APending Publication Date: 2025-01-21NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424319.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The residual lithium compound on the surface of high-nickel ternary positive electrode material is difficult to eliminate, resulting in poor battery storage performance, susceptible to electrolyte corrosion, and poor circulation stability.

Method used

By wrapping the organic cobalt compound and oxygen source on the surface of the high-nickel ternary cathode material, a coating layer of cobalt tetroxide is formed to eliminate residual alkali.

Benefits of technology

The cobalt tetroxide coating layer improves the conductivity of the material, enhances cycle stability and thermal stability, and improves battery performance in fast charging and high power output scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330413A_ABST
    Figure CN119330413A_ABST
Patent Text Reader

Abstract

The invention discloses a method for eliminating residual alkali of a high-nickel ternary positive electrode material, and belongs to the technical field of lithium ion batteries. The method for eliminating the residual alkali of the high-nickel ternary positive electrode material comprises the step of coating the surface of the high-nickel ternary positive electrode material with an organic cobalt compound and an oxygen source to form a cobaltosic oxide coating layer so as to eliminate the residual alkali of the high-nickel ternary positive electrode material. The cobaltosic oxide wrapping layer formed in the method for eliminating the residual alkali of the high-nickel ternary positive electrode material not only can consume a residual lithium compound on the surface of the high-nickel ternary positive electrode material, but also can inhibit side reactions at a positive electrode and an electrolyte surface, so that the positive electrode material is effectively protected from being eroded by the electrolyte; the cycling stability, the conductivity and the thermal stability of the material can be enhanced; the method for eliminating the residual alkali is simple to operate and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-ion batteries, and in particular relates to a method for eliminating residual alkali in a high-nickel ternary positive electrode material. Background Art

[0002] At present, the development of high-capacity and high-energy-density battery electrodes is one of the key research directions for the next generation of lithium-ion batteries. High-nickel ternary cathode materials have excellent theoretical specific capacity (>200mAg –1 ) and has attracted widespread attention. However, the rapid capacity decay and poor storage performance of high-nickel ternary positive electrode materials are the main problems of all high-nickel LiNi 1-x-y Co y Mn z Intrinsic problems of O2 (1–x–y>0.5) materials. The high-valent and unstable Ni in high-nickel ternary materials during the electrochemical cycle 3+ / Ni 4+ , which is the main reason for its capacity decay and poor storage performance. Secondly, HF is produced when the electrolyte is hydrolyzed, and the reaction equation is: LiPF6+H2O→POF3+2HF+LiF; HF is a highly corrosive acid, which can react with the metal ions in the positive electrode material, causing the structure of the positive electrode material to change, destroying the stability of its crystal structure, seriously affecting the battery performance, causing battery capacity decay, shortened cycle life and other problems.

[0003] In addition, the formation of residual lithium compounds Li2CO3 / LiOH layer (residual alkali) on the surface of high-nickel ternary cathode materials is another key reason for the poor storage performance of batteries. In the synthesis process of high-nickel ternary cathode materials, it is inevitable to add excessive Li, which will leave lithium oxide on the surface. During storage, it is easy to absorb CO2 and H2O in the air to form Li2CO3 / LiOH layer. Moreover, Ni 3+ Slowly and spontaneously reduced to Ni 2+ , resulting in rapid water absorption, which in turn promotes the formation of Li2CO3 / LiOH. 2+ The irreversible migration of Li2CO3 / LiOH layer and NiO-type rock salt phase is easy to produce NiO-type rock salt phase on the surface of high nickel ternary cathode material, which leads to cathode degradation and increased impedance. Both Li2CO3 / LiOH layer and NiO-type rock salt phase have no electrochemical activity during lithium insertion and extraction, blocking Li + Diffusion channels will lead to a decrease in capacity. More importantly, these impurities may cause gas release and other safety issues during battery operation. How to eliminate such residual alkaline impurities and enhance the cycle stability and electrochemical activity of the material is one of the unresolved issues. Summary of the invention

[0004] The problem to be solved by the present invention is to provide a method for eliminating residual alkali in high-nickel ternary positive electrode materials to solve the problems that residual lithium compounds on the surface of high-nickel ternary positive electrode materials are difficult to eliminate, the positive electrode materials are easily corroded by electrolytes, and the cycle stability is poor.

[0005] The technical solution adopted to solve the technical problem is to provide a method for eliminating residual alkali in high-nickel ternary positive electrode materials, by wrapping organic cobalt compounds and oxygen sources on the surface of the high-nickel ternary positive electrode materials to form a cobalt tetroxide coating layer to eliminate the residual alkali in the high-nickel ternary positive electrode materials.

[0006] The beneficial effects of the above technical solution adopted in the present invention are as follows: cobalt tetraoxide (Co3O4) has relatively high electronic conductivity; at the same time, Co3O4 can also react with some residual lithium on the surface of the high-nickel ternary positive electrode material itself to generate a LiCoO2 / Co3O4 composite coating layer, so that the high-nickel ternary positive electrode material treated in this way has good conductivity during the battery charging and discharging process, which helps to transmit electrons more quickly, reduces the internal resistance of the battery, and enables the battery to show better performance under high current charging and discharging conditions, such as having more significant advantages in fast charging and high power output scenarios. Compared with traditional metal oxide coatings such as Al2O3, ZrO2, TiO2 and WO3 with relatively poor electronic conductivity, the rate performance of the battery can be improved to a certain extent.

[0007] Preferably, the method for eliminating residual alkali of high-nickel ternary positive electrode material comprises the following steps:

[0008] (1) ionizing an oxygen source into oxygen plasma, and using oxygen plasma and an organic cobalt compound as precursors to alternately deposit on the surface of a high-nickel ternary cathode material to form a cobalt oxide coating layer;

[0009] (2) The high-nickel ternary positive electrode material with a cobalt tetroxide coating layer formed on the surface is annealed to eliminate the residual alkali in the high-nickel ternary positive electrode material.

[0010] The beneficial effects of the above technical solution adopted by the present invention are as follows: in the present invention, the oxygen source is ionized into oxygen plasma, and the precursor is used as a precursor with an organic cobalt compound, and the precursor pulse is sequentially introduced into the chamber through an inert gas, and then a thin film is deposited on the substrate through a continuous self-limiting reaction, and then the excess unreacted precursor and reaction byproducts are purged out of the chamber, and the next precursor sub-cycle is entered, and the above steps are continuously repeated, alternately cycled, and a single-phase Co3O4 thin film is obtained layer by layer, and Co3O4 can be wrapped on the surface of the high-nickel ternary positive electrode material at a relatively low temperature; the high-nickel ternary positive electrode material wrapped with Co3O4 is annealed in the air to eliminate the residual alkali of the high-nickel ternary positive electrode material. The Co3O4 wrapping layer can not only inhibit the side reaction at the positive electrode / electrolyte interface, protect the high-nickel ternary positive electrode material from HF erosion, improve the structural stability of the material, and then enhance the cyclic stability of the material, but also consume the residual alkali on the surface of the high-nickel ternary positive electrode material, enhance the conductivity of the high-nickel ternary positive electrode material, and effectively improve the electrochemical performance of the high-nickel ternary positive electrode material.

[0011] Preferably, the oxygen source is at least one of oxygen, water and hydrogen peroxide.

[0012] More preferably, the oxygen source is oxygen gas.

[0013] The beneficial effects of the technical solution adopted in the present invention are: oxygen is ionized into plasma, the activity of the reactants is enhanced, the reaction is made more complete, and the Co3O4 coating layer can be deposited at a lower temperature.

[0014] Preferably, the organic cobalt compound is at least one of dicarbonyl cyclopentadienyl cobalt, cobalt cyclopentadienyl, cobalt biscyclopentadienyl, cobalt isooctanoate and cobalt carbonyl tert-butyl acetylide.

[0015] Preferably, the high-nickel ternary positive electrode material in step (1) is a nickel cobalt manganese oxide lithium NCM811 material with a particle size of 1 to 10 μm.

[0016] Preferably, the radio frequency power of ionization in step (1) is 250 to 350 W.

[0017] Preferably, the alternating deposition in step (1) comprises the following steps: alternatingly depositing oxygen plasma and an organic cobalt compound for a total of 30 to 50 times in an inert atmosphere at 200 to 250° C. and a vacuum degree of ≤10 Pa.

[0018] More preferably, the alternating deposition process is: pulse of the organic cobalt compound for 0.1 s, wait for 10 s, purge for 20 s, pulse of the oxygen plasma for 1 s, wait for 10 s, purge for 20 s, and the alternating deposition process is repeated 30 to 50 times.

[0019] Preferably, the thickness of the cobalt tetroxide coating layer in step (1) is 20 to 50 nm.

[0020] Preferably, the annealing treatment in step (2) is carried out at a temperature of 600-650° C. for 4-6 hours; and the annealing treatment is carried out in an air atmosphere.

[0021] More preferably, the heating rate of the annealing treatment is 5 to 10° C. / min.

[0022] The present invention has the following beneficial effects:

[0023] The Co3O4 coating layer formed in the method for eliminating residual alkali from high-nickel ternary positive electrode materials of the present invention can not only consume residual lithium compounds on the surface of the high-nickel ternary positive electrode materials, but also inhibit side reactions at the positive electrode / electrolyte interface, effectively protect the positive electrode materials from corrosion by the electrolyte, and enhance the material's cycle stability, conductivity and thermal stability; and the residual alkali elimination method is simple to operate and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a flow chart of a method for eliminating residual alkali from high-nickel ternary cathode materials;

[0025] Figure 2 HRTEM images of the modified 50Co3O4-NCM material obtained in Example 1 at different magnifications;

[0026] Figure 3 The EDS element distribution diagram of the modified 50Co3O4-NCM material obtained in Example 1; wherein (a) is the Ni element distribution diagram; (b) is the Co element distribution diagram; (c) is the Mn element distribution diagram;

[0027] Figure 4 This is the Raman spectrum of the modified 50Co3O4-NCM material obtained in Example 1;

[0028] Figure 5 Cycling performance diagram of NCM811, 30Co3O4-NCM and 50Co3O4-NCM electrodes at 1C;

[0029] Figure 6 Cycling performance diagram of NCM811, 30Co3O4-NCM and 50Co3O4-NCM electrodes at 5C;

[0030] Figure 7 The rate performance diagram of NCM811, 30Co3O4-NCM and 50Co3O4-NCM electrodes;

[0031] Figure 8 EIS spectra of NCM811, 30Co3O4-NCM and 50Co3O4-NCM electrodes. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below in conjunction with the examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The nickel cobalt manganese oxide lithium NCM811 material comes from Shenzhen Youyan Technology Co., Ltd.

[0033] Example 1

[0034] A method for eliminating residual alkali in a high-nickel ternary positive electrode material comprises the following steps:

[0035] (1) Spreading a nickel cobalt manganese oxide NCM811 material with a particle size of 5 μm on a tray and placing it in a reaction chamber; ionizing oxygen at a radio frequency power of 300 W to form oxygen plasma, heating dicyclopentadiene cobalt to 100° C., using oxygen plasma and dicyclopentadiene cobalt as precursors, alternately depositing oxygen plasma and dicyclopentadiene cobalt on the surface of the high-nickel ternary cathode material in a nitrogen atmosphere at 230° C. and a vacuum degree of 5 Pa, the deposition process is: dicyclopentadiene cobalt pulse 0.1 s, wait 10 s, purge 20 s, oxygen plasma pulse 1 s, wait 10 s, purge 20 s, the deposition process is repeated 50 times to form a cobalt tetroxide coating layer with a thickness of 40 nm;

[0036] (2) The lithium nickel cobalt manganese oxide NCM811 material with a cobalt tetroxide coating layer formed on the surface is naturally cooled and transferred to a porcelain crucible, and then placed in a tubular furnace; it is heated to 600°C at a heating rate of 5°C / min in compressed air and kept warm for 5 hours for annealing treatment. After cooling to room temperature, the modified 50Co3O4-NCM material is obtained, which can achieve the elimination of residual alkali in the high-nickel ternary positive electrode material.

[0037] The process of the method for eliminating residual alkali of high nickel ternary positive electrode material in this embodiment is as follows Figure 1 The modified 50Co3O4-NCM material was subjected to HRTEM test, EDS mapping test and Raman spectrum test. The test results are shown in Figures 2 to 4 As shown by Figure 2 It can be seen that there is a modified layer on the surface of NCM811 particles, which is characterized by an amorphous structure, and its thickness is about 40nm. Figure 3 It can be seen that Ni, Co and Mn elements are evenly distributed inside NCM811, and Co element is evenly distributed on the surface of NCM811, which confirms that there is a Co3O4 coating layer on the surface of NCM811 material and the coating layer is very uniform. Figure 4 It can be observed that at 535.19cm –1The characteristic peak of Co3O4 that appears at the NCM811 surface proves that the Co3O4 coating layer is successfully coated on the NCM811 surface.

[0038] Example 2

[0039] A method for eliminating residual alkali in a high-nickel ternary positive electrode material comprises the following steps:

[0040] (1) Spreading a nickel cobalt manganese oxide NCM811 material with a particle size of 5 μm on a tray and placing it in a reaction chamber; ionizing oxygen at a radio frequency power of 300 W to form oxygen plasma, heating dicyclopentadiene cobalt to 100° C., using oxygen plasma and dicyclopentadiene cobalt as precursors, alternately depositing oxygen plasma and dicyclopentadiene cobalt on the surface of the high-nickel ternary cathode material in a nitrogen atmosphere at 230° C. and a vacuum degree of 5 Pa, the deposition process is: dicyclopentadiene cobalt pulse 0.1 s, wait 10 s, purge 20 s, oxygen plasma pulse 1 s, wait 10 s, purge 20 s, and the deposition process is repeated 30 times to form a cobalt tetroxide coating layer with a thickness of 25 nm;

[0041] (2) The lithium nickel cobalt manganese oxide NCM811 material with a cobalt tetroxide coating layer formed on the surface is naturally cooled and transferred to a porcelain crucible, and then placed in a tubular furnace; it is heated to 600°C at a heating rate of 5°C / min in compressed air and kept warm for 5 hours for annealing treatment. After cooling to room temperature, the modified 30Co3O4-NCM material is obtained, which can achieve the elimination of residual alkali in the high-nickel ternary positive electrode material.

[0042] Example 3

[0043] A method for eliminating residual alkali in a high-nickel ternary positive electrode material comprises the following steps:

[0044] (1) Spreading a nickel cobalt manganese oxide NCM811 material with a particle size of 1 μm on a tray and placing it in a reaction chamber; ionizing oxygen at a radio frequency power of 350 W to form oxygen plasma, heating dicarbonyl cyclopentadienyl cobalt to 100° C., using oxygen plasma and dicarbonyl cyclopentadienyl cobalt as precursors, alternately depositing oxygen plasma and dicarbonyl cyclopentadienyl cobalt on the surface of the high-nickel ternary positive electrode material in a nitrogen atmosphere at 250° C. and a vacuum degree of 10 Pa, the deposition process is: dicarbonyl cyclopentadienyl cobalt pulse 0.1 s, wait 10 s, purge 20 s, oxygen plasma pulse 1 s, wait 10 s, purge 20 s, the deposition process is repeated 40 times to form a cobalt tetroxide coating layer with a thickness of 30 nm;

[0045] (2) The lithium nickel cobalt manganese oxide NCM811 material with a cobalt tetroxide coating layer formed on the surface is naturally cooled and transferred to a porcelain crucible, and then placed in a tubular furnace; it is heated to 650°C at a heating rate of 7°C / min in compressed air and kept warm for 6 hours for annealing treatment. After cooling to room temperature, the modified 40Co3O4-NCM material is obtained, which can achieve the elimination of residual alkali in the high-nickel ternary positive electrode material.

[0046] Example 4

[0047] A method for eliminating residual alkali in a high-nickel ternary positive electrode material comprises the following steps:

[0048] (1) Spreading a nickel cobalt manganese oxide NCM811 material with a particle size of 10 μm on a tray and placing it in a reaction chamber; ionizing oxygen at a radio frequency power of 250 W to form oxygen plasma, heating cobalt cyclopentaneate to 100° C., using oxygen plasma and cobalt cyclopentaneate as precursors, alternately depositing oxygen plasma and cobalt cyclopentaneate on the surface of the high-nickel ternary positive electrode material in a nitrogen atmosphere at 200° C. and a vacuum degree of 1 Pa, the deposition process is: cobalt cyclopentaneate pulse 0.1 s, wait 10 s, purge 20 s, oxygen plasma pulse 1 s, wait 10 s, purge 20 s, the deposition process is repeated 30 times, and a cobalt oxide coating layer with a thickness of 25 nm is formed;

[0049] (2) The lithium nickel cobalt manganese oxide NCM811 material with a cobalt tetroxide coating layer formed on the surface is naturally cooled and transferred to a porcelain crucible, and then placed in a tubular furnace; it is heated to 630°C at a heating rate of 10°C / min in compressed air and kept warm for 4 hours for annealing treatment. After cooling to room temperature, the modified 30Co3O4'-NCM material is obtained, which can achieve the elimination of residual alkali in the high-nickel ternary positive electrode material.

[0050] Experimental example

[0051] 1. The residual alkali content on the surface of the nickel cobalt manganese oxide NCM811 material after the residual alkali elimination of Examples 1 to 2 and the nickel cobalt manganese oxide NCM811 material without any treatment were analyzed. The analysis method is shown in "GB / T 41704-2022 Lithium Ion Battery Positive Electrode Material Test Method Determination of Magnetic Foreign Matter Content and Residual Alkali Content", and the results are shown in Table 1.

[0052] Table 1 Comparison of residual alkali content on material surface

[0053]

[0054] It can be seen from Table 1 that the residual alkali content on the surface of the lithium nickel cobalt manganese oxide NCM811 material without any treatment is high, which not only affects the thermal stability of NCM811, but also hinders the +The diffusion of the nickel cobalt manganese oxide NCM811 material affects its electrochemical performance. The residual alkali content of the nickel cobalt manganese oxide NCM811 material treated by the method of the present invention is significantly reduced, and the nickel cobalt manganese oxide NCM811 material after the residual alkali is eliminated can also have excellent electrochemical performance.

[0055] 2. Assembly of button battery

[0056] The nickel cobalt manganese oxide NCM811 material after the residual alkali is eliminated in Examples 1 and 2 and the nickel cobalt manganese oxide NCM811 material without any treatment are respectively assembled into button batteries, and the specific process is as follows:

[0057] (1) The positive electrode material was prepared using the nickel cobalt manganese oxide NCM811 material after the residual alkali was eliminated in Examples 1 to 2 and the nickel cobalt manganese oxide NCM811 material without any treatment: 0.435 g, 0.05 g and 0.015 g of the nickel cobalt manganese oxide NCM811 material, conductive carbon black and polyvinylidene fluoride were weighed in a mass ratio of 87:10:3 and placed in a ball mill, and N-methylpyrrolidone was added as a solvent and ball milled for 3 h to prepare a uniform slurry, the slurry was coated on the surface of aluminum foil, and vacuum dried at 60° C. and 110° C. for 12 h respectively, and then cut into 30Co3O4-NCM electrodes, 50Co3O4-NCM electrodes and NCM811 electrodes of appropriate sizes as positive electrode sheets;

[0058] (2) Assembly of button cells: Using metallic lithium as the negative electrode, a polypropylene film as the separator, and 1M LiPF6 in EC / EMC (volume ratio of 3:7) as the electrolyte, button cells were assembled in a glove box with a water and oxygen concentration of less than 0.01 ppm to obtain 30Co3O4-NCM batteries, 50Co3O4-NCM batteries, and NCM batteries, respectively.

[0059] 3. Electrochemical performance test

[0060] The electrochemical performance of 30Co3O4-NCM battery, 50Co3O4-NCM battery and NCM battery was tested using the Blue Electric battery test system. The test conditions were: ambient temperature 25°C, voltage range 2.7-4.3V, current 1C=mAg –1 .

[0061] Test results such as Figures 5 to 8 As shown. Figure 5 It can be seen that the initial discharge capacity of the NCM811 positive electrode is 152.9 mAhg –1 After 200 cycles, the discharge capacity dropped to 85.3 mAh g –1 The capacity retention rate is 55.79%. In contrast, the initial discharge specific capacities of 30Co3O4-NCM and 50Co3O4-NCM cathodes are 169.1 mAh g–1 and 169.8mAh g –1 After 200 cycles, the capacity is stable at 136.7 mAh g –1 and 113.1mAh g –1 , and the capacity retention rates are 80.84% ​​and 66.61%. This indicates that the Co3O4 / LiCoO2 composite coating formed after the residual alkali elimination method of the high-nickel ternary positive electrode material of the present invention can effectively prevent the electrolyte and the single crystal NCM811 positive electrode particles from directly contacting and causing serious side reactions, and inhibit the dissolution of transition metals from the positive electrode material, thereby improving the structural stability and cycle stability of the NCM811 material.

[0062] Figure 6 The cycling stability of NCM811, 30Co3O4-NCM and 50Co3O4-NCM cathodes at room temperature in the voltage range of 2.7 to 4.3 V at a current density of 5C is presented. The initial discharge capacity of the NCM811 electrode is 97.6 mAh g –1 After 200 cycles, the capacity is stable at 68.5 mAh g –1 The capacity retention rate is 70.18%. The initial discharge specific capacities of 30Co3O4-NCM electrode and 50Co3O4-NCM electrode are 133.1 and 117.7 mAh g –1 After 200 cycles, the capacities are stabilized at 101.3 and 95.6 mAh g –1 , the capacity retention rates were 76.11% and 81.22% respectively.

[0063] from Figure 7 The rate performance of NCM811, 30Co3O4-NCM and 50Co3O4-NCM at room temperature can be seen in the figure. As the current density increases from 0.1C to 5C, the discharge specific capacities of 30Co3O4-NCM electrode are 220.5, 212.4, 199.4, 188.2, 172.6 and 142 mAh g, respectively. –1 The discharge specific capacities of 50Co3O4-NCM electrodes are 160.4, 191.7, 177.8, 166.8, 147.8 and 121.9 mAh g –1 In comparison, the discharge capacity decay of NCM811 coated with Co3O4 is smaller and it always outperforms the performance of NCM811 electrode at various current densities.

[0064] Figure 8 The EIS spectra of NCM811, 30Co3O4-NCM and 50Co3O4-NCM electrodes at room temperature are shown in Figure 2. Figure 8This indicates that Co3O4 wrapping is beneficial to enhancing the ionic conductivity and electronic conductivity of the material, which also explains its better electrochemical performance, especially the cycling performance at high current 5C.

[0065] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A method for eliminating residual alkali in high-nickel ternary positive electrode materials, characterized in that: The residual alkali of the high-nickel ternary positive electrode material is eliminated by wrapping the organic cobalt compound and the oxygen source on the surface of the high-nickel ternary positive electrode material to form a cobalt tetroxide coating layer.

2. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) ionizing an oxygen source into oxygen plasma, and using oxygen plasma and an organic cobalt compound as precursors to alternately deposit on the surface of a high-nickel ternary cathode material to form a cobalt oxide coating layer; (2) The high-nickel ternary positive electrode material with a cobalt tetroxide coating layer formed on the surface is annealed to eliminate the residual alkali in the high-nickel ternary positive electrode material.

3. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The oxygen source is at least one of oxygen, water and hydrogen peroxide.

4. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The organic cobalt compound is at least one of dicarbonyl cyclopentadienyl cobalt, cobalt cyclopentadienyl, cobalt dicyclopentadienyl, cobalt isooctanoate and cobalt carbonyl tert-butyl acetylide.

5. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The high-nickel ternary positive electrode material in step (1) is a nickel cobalt manganese oxide NCM811 material with a particle size of 1 to 10 μm.

6. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The radio frequency power of ionization in the step (1) is 250-350W.

7. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The alternating deposition in step (1) comprises the following steps: in an inert atmosphere at 200-250° C. and a vacuum degree of ≤10 Pa, oxygen plasma and an organic cobalt compound are alternately deposited for a total of 30-50 times.

8. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The thickness of the cobalt tetroxide coating layer in the step (1) is 20 to 50 nm.

9. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 2, characterized in that: The annealing treatment in step (2) is carried out at a temperature of 600 to 650° C. for 4 to 6 hours; the annealing treatment is carried out in an air atmosphere.

10. The method for eliminating residual alkali of high-nickel ternary positive electrode material according to claim 9, characterized in that: The heating rate of the annealing treatment is 5-10°C / min.